Decoding Western Festive Season Symbols and Rituals in Marketing Messages: A Bottom of the Pyramid Consumer Study in South Africa. Issue 1 (2nd January 2020) - Lappeman, James; Zornitta, Chloë; Mowzer, Zeenat
Abstract: This study explored the communication of marketing messages containing traditional, Western festive season symbols and rituals. Specifically, the research sought to understand the decoding of such messages portraying festive season symbols (like Santa Claus and Christmas trees) and rituals, by Afrocentric bottom of the pyramid (BOP) consumers. This qualitative study involved interviews with thirty-one participants in two metropolitan areas in South Africa. The study used a combination of semi-structured interview questions and treatments of two South African television advertisements and two newspaper advertisements depicting Western festive season symbols and rituals. The study revealed a broadly positive sentiment towards the festive season, where festive season activities allow participants to implement their Afrocentric cultural values of unity and collective responsibility. Findings also show that Afrocentric cultural values do affect the decoding of these marketing messages. There was also a variety of responses to marketing messages displaying the symbols of Christmas trees and Santa Claus, which were not common in BOP consumer households. The key recommendation highlighted by this study is that marketing messages communicated to South African BOP consumers should also consider Afrocentric values of unity and collective responsibility.